Penggunaan Aplikasi Pendeteksi Olahraga berbasis Global Positioning System (GPS) untuk Meningkatkan Aktivitas Fisik Masyarakat - Musridho, Raja Joko; Priyatno, Arif Mudi; Ramadhan, Wahyu Febri (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
The lack of physical activity in society has become one of the main factors contributing to the increased risk of non-communicable diseases. GPS-based technology has rapidly developed and can be utilized to enhance motivation for exercising. This community service program aims to educate and assist the public in using GPS-based exercise tracking applications to increase their physical activity. The methods used include socialization, training, monitoring of application usage, and evaluation of its effectiveness. The results indicate that the application helps raise awareness and motivation for exercising, as evidenced by the increased frequency and duration of physical activity. Thus, the use of GPS-based exercise tracking applications can be an innovative solution for promoting a healthier lifestyle in society.